5.3.4-eg - 7 2 f ( x ) dx + Z 9 7 f ( x ) dx = Z 9 2 f ( x...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Example Find a and b so that Z 7 - 1 f ( x ) dx - Z 2 - 1 f ( x ) dx + Z 9 7 f ( x ) dx = Z b a f ( x ) dx. Solution: Using the identity Z d c f ( x ) dx = Z K c f ( x ) dx + Z d K f ( x ) dx, it follows that Z 7 - 1 f ( x ) dx - Z 2 - 1 f ( x ) dx = Z 7 2 f ( x ) dx, and Z
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 7 2 f ( x ) dx + Z 9 7 f ( x ) dx = Z 9 2 f ( x ) dx. Thus, a = 2 , b = 9 ....
View Full Document

This note was uploaded on 04/02/2012 for the course MTH 132 taught by Professor Kihyunhyun during the Fall '10 term at Michigan State University.

Ask a homework question - tutors are online